The manufacturing industry in Iraq (1990-2020): Reality and possibilities - AbdelKarim, Amna (Al-Adab Journal, 2023)
The transformative industry is the basis for which any economic development depends on being the activity that contributes to providing machines, equipment and devices for all economic sectors and turns them into modern sectors, and therefore any economic construction is ever for it from a base of manufacturing industries that feed it with its need for modern and changing machines and devices to keep pace with the requirements of the times and its progress In addition to providing consumer goods, as the manufacturing industry is one of the most important foundations on which economic progress is based and represents the base of social development in its various aspects, as the manufacturing industry leads to expansion in the economic jobs of the country and adds to its tasks other tasks such as planning for industry and economy and solving new problems that result from industrial construction Or it requires awareness of it and finding appropriate solutions to them. In its methodology, the study relied on several basic approaches in writing the research, in order to reach the best results, and among these approaches is the historical approach, which relied in its study on the historical narrative and an indication of a series of time periods that the manufacturing industry went through in Iraq for the period (1990-2020) in order to identify On the developments and changes that took place during that period between the rise and fall in the number of industrial establishments from year to year, depending on a number of political and economic factors that Iraq went through. And the inductive approach that is concerned with all the data and information obtained from the field study to study the industrial growth of the manufacturing industries in Iraq. The ownership and sizes of industrial facilities for manufacturing industries in Iraq for the period (1990-2020) were also studied. The study reached several conclusions: 1- The period between (1990-2002) witnessed a clear fluctuation in the number of manufacturing industries at the official level due to the economic blockade, as the value of the output of the commodity sectors declined and economic growth rates declined, which reflects a continuous deterioration in real production. 2- Very difficult economic and political circumstances occurred during the stage between the years (2003-2020), which clearly affected the weakening of industrial activity, which was the decline in the contribution of the manufacturing industry to the gross domestic product, as well as the decline in the industrial work force compared to what it was in 1990 due to the stopping of most large industrial facilities from Production. 3- When using the standards of the industry known from the number of industrial establishments, the number of workers, the wages of workers, the value of industrial production, the value of production requirements and the added value to study industrial growth in Iraq, it became clear to us that the manufacturing industry has passed in many stages between the rise and decrease in these standards between one year without another, and the reason for this is due to the events The policy that Iraq went through during this period, which was reflected in the manufacturing industry. 4- Industrial activity in Iraq is distributed in terms of ownership between the public sector, the cooperative sector, the private sector, the government sector and the mixed sector (Iraqi + foreign), as the ownership of industrial establishments for the private sector is the most number of other sectors. 5- We note in the sizes of the industrial facilities of manufacturing industries in Iraq for the period (1990-2020) that the large facilities have made progress in the number of workers, total wages, production value and added value, and achieved profits that exceeded medium and small enterprises, and this is due to government support for large facilities and the provision of raw materials at subsidized prices as well as the availability of Production requirements and the lowest costs. As for the intermediate facilities, they achieved only a small percentage, while we find that the small facilities, despite the high number of their industrial facilities during those years, are low, but the number of workers is low compared to large facilities, as well as other criteria, in which only a small percentage achieved.